(untitled) (قضايا سياسية, 2022)
The Iranian –Turkish relations in the region can be considered as the most interacted relations , due to the nature of that movement between the two states among the whole regional interaction in the region . The two states started their relations during the last centuries based on the mutual strategic interests which overcome the points of cooperation on the point of differences , specially that each state understand the importance , the second side on most the interaction of the region , and each of then considered as important issue which cannot be abandoned in confronting the regional and international challenges . In spite that the strategic between the two states filt the balance in the side of the cooperation and compatibility , never less there are many issues of differences and the ways to deal with it . There are many obstacles east shadow over these relations since they the two countries collide and alliance conflict between them . The tools the use differ in dominating the region , whether military ,as in the Iranian case , or political and economy , as in the case with turkey .It is clear that the conflict, cooperation and expansion are an going condition shaping the relations between the two countries . In spite of some historical periods that witnessed an important rapprochement between the two countries , the sought to prove their existence and that the possessed strategies that not be over looked . This means that both of them can ignore the other side in international and regional interactions , de spits the competition between them which stems from a full awareness of their roles in the region . The strategic movement between the two countries has tended towards consolidating the bonds of strategic partnership between them , based on their full awareness that this situation constitute an added force for them in light of increasing regional and international challenges facing them .